The housekeeper and the professor [compact disc, unabridged] - Ogawa, Yōko, 1962- (Tantor Media, Inc., 2013)
He is a brilliant math Professor with a peculiar problem-ever since a traumatic head injury; he has lived with only eighty minutes of short-term memory. She is an astute young Housekeeper-with a ten-year-old son-who is hired to care for the Professor. And every morning, as the Professor and the Housekeeper are introduced to each other anew, a strange and beautiful relationship blossoms between them.